FEMALE INTELLECTUALITY AND READERSHIP IN VICTORIAN BRITAIN. - MANDICI, Mădălina Elena (Studii de Ştiintă şi Cultură, 2022)
This paper focuses on Victorian British female writers and readers who helped define (at least partially and incipiently) the acquisition of literacy skills, literary aesthetics and women’s roles within the society at large. Victorian women’s way of exercising literacy and constructing female characters enamored by fiction provided the impetus for the intellectual autonomy of professional women. The didactic potential of fiction penned by women as a splithalf answer to questions regarding printed texts as nugatory or purposeful engages two directions, echoing the long line of medical literature, periodicals, essays and propaganda literature addressing this dilemma per se. Could and should the reading habits of those with minds uninstructed by experience gainsay the possibility of fiction to educate individuals – women in particular – without veering them away from virtues such as humility, chastity, obedience and silence? These questions lend themselves to no facile answers, although they frame the minds and the dilemmas of nineteenth-century novelists who set forth to include quarrelsome, independent-minded female characters in their fiction.